The Social Dynamics of Collective Action: Evidence from the Captain Swing Riots, 1830-31 - Toke Aidt; Gabriel Leon; Max Satchell (Center for Economic Studies and ifo Institute (CESifo), 2017)
Social unrest often erupts suddenly and diffuses quickly. What drives people to overcome their collective action problem and join a riot or protest, turning what is initially a small event into a widespread movement? We address this question by examining the Swing riots of 1830-31. The communication constraints of the time induced spatio-temporal variation in exposure to news about the uprising, allowing us to estimate the role of contagion in the spread of the riots. We find that local (rather than national) sources of information were central in driving contagion, and that this contagion magnified the impact that social and economic fundamentals had on riots by a factor of 2.65. Our historical data allow us to overcome a number of econometric challenges, but the Swing riots are of independent interest as well: they contributed to the passage of the Great Reform Act, a key step in Britain's institutional development.
Keywords: D72; D74; O16; 330; riots; diffusion; conflict; contagion; Captain Swing